Extended Tauberian Theorem for the weighted mean Method of Summability - Çanak, І.; Totur, Ü. (Ukrains’kyi Matematychnyi Zhurnal, 2013)
We prove a new Tauberian-like theorem. For a real sequence u = (u n ), on the basis of the weighted mean summability of its generator sequence (V (0) n,p (∆u)) and some other conditions, this theorem establishes the property of slow oscillation of the indicated sequence.